PENGARUH KONFLIK KERJA-KULIAH MINGGUAN TERHADAP KELELAHAN DENGAN KUALITAS TIDUR SEBAGAI PEMEDIASI PADA MAHASISWA DAN MAHASISWI STIE KEBANGSAAN DI BIREUEN - Amri, Mirza Dwi Putra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This study aims to determine the Influence of Work Conflict Weekly Toward Fatigue With Sleep Quality As A Mediator At Student And Student STIE Nationality InBireuen. Samples taken in this research are students and students of STIE Kebangsaan in Bireun. And the respondents are taken is a student or student aged at least 18 years with part time work. This research method used questionnaires as research instruments, with the number of questionnaires successfully analyzed as many as 100 questionnaires. the sampling technique used is non-probability sampling, this technique is used to determine the profoundness of elements in the population to be selected as unknown samples, and the type used is purposive, where the population has certain characteristics that can be used as respondents. data obtained from respondents through questionnaires, tabulated using Microsoft Office Excel for statistical analysis with computer tools IBM SPSS Program version 20 Windows. The results showed that there was a significant relationship between the mediation variable and the dependent variable and the larger dependent variable on the mediation variable and the greater beta value in the second equation and the third equation.Keywords: Fatigue, Sleep Quality, Work-School Conflict.